2022
DOI: 10.22146/jsv.59711
|View full text |Cite
|
Sign up to set email alerts
|

Improve the Performances of Broilers as Reduce Heat Stress by the Supplementation Jaloh (Salix tetrasperma Roxb) in Drinking Water

Abstract: Abstrak Pencegahan dampak cekaman panas pada ayam broiler dapat dilakukan dengan pemberian ekstrak tanaman yang juga berguna dalam pengembangan obat-obat tradisional sebagai alternatif pengurangan penggunaan bahan-bahan kimiawi. Tujuan penelitian ini adalah untuk mengevaluasi performan ayam broiler yang diberikan ekstrak daun jaloh melalui air minum. Penelitian dilakukan di Laboratorium Lapangan Peternakan (LLP), Jurusan Peternakan, Fakultas Pertanian, Universitas Syiah Kuala. Sebanyak 80 ekor anak ayam broile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The current study's findings are consistent with those found ( Al-Fataftah and Abdelqader, 2013 ), which showed an improvement in the final body weight ( FBW ), average daily weight gain and FCR of broiler chicks given 100 mL of willow leaf extract per day. Additionally, an increase in BWG and FBW occurred in broiler chicks that received willow ( S. tetrasperma ) leaf extract in drinking water under heat stress at 5 wk of age ( Zulfan et al, 2022 ). Also, according to Kalia et al (2021) , the synergistic action of salicin, caffeic acid, and polyphenols boosted feed utilization, feed conversion rate and chicken growth in broiler chicks fed a diet enhanced with willow leaf extract 300 mg/kg BW in the cold desert.…”
Section: Discussionmentioning
confidence: 99%
“…The current study's findings are consistent with those found ( Al-Fataftah and Abdelqader, 2013 ), which showed an improvement in the final body weight ( FBW ), average daily weight gain and FCR of broiler chicks given 100 mL of willow leaf extract per day. Additionally, an increase in BWG and FBW occurred in broiler chicks that received willow ( S. tetrasperma ) leaf extract in drinking water under heat stress at 5 wk of age ( Zulfan et al, 2022 ). Also, according to Kalia et al (2021) , the synergistic action of salicin, caffeic acid, and polyphenols boosted feed utilization, feed conversion rate and chicken growth in broiler chicks fed a diet enhanced with willow leaf extract 300 mg/kg BW in the cold desert.…”
Section: Discussionmentioning
confidence: 99%